Analisis Peran Guru dalam Strategi Pembelajaran Anak Berkebutuhan Khusus di Kelas 2 SDN Sadeng 03 - Mayangsari, Arum; Astuti, Tri; Hanifatunnisa, Maulfi; Irafany, Marcella Nadya; Az zahro, Ilma; Divanggi, Ainida (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the role of teachers in learning strategies for children with special needs in grade 2 of SDN Sadeng 03. This study uses a qualitative descriptive method with a case study approach, involving observation, interviews, and document analysis. The results of the study indicate that teachers hold five important roles, namely as demonstrator, facilitator, mediator, evaluator, and motivator in learning for children with special needs. The learning strategies applied include the use of concrete and visual media, positive reinforcement, curriculum adaptation, independence training, and exploration of children's interests and talents. This study also reveals various obstacles faced, such as curriculum incompatibility, minimal social interaction, lack of teacher training, and limited communication with parents. In conclusion, the role of adaptive and collaborative teachers is crucial in creating an inclusive learning environment, and support from schools and parents is needed so that education for children with special needs can be implemented optimally.